2022
DOI: 10.1037/amp0000895
|View full text |Cite
|
Sign up to set email alerts
|

Patient and provider predictors of telemental health use prior to and during the COVID-19 pandemic within the Department of Veterans Affairs.

Abstract: The current study examined patient and provider differences in use of phone, video, and in-person mental health (MH) services. Participants included patients who completed ≥1 MH appointment within the Department of Veterans Affairs (VA) from 10/1/17–7/10/20 and providers who completed ≥100 VA MH appointments from 10/1/17–7/10/20. Adjusted odds ratios (aORs) are reported of patients and providers: (a) completing ≥1 video MH appointment in the pre-COVID (10/1/17–3/10/20) and COVID (3/11/20–7/10/20) periods; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 44 publications
1
53
1
Order By: Relevance
“…Indeed, COVID-19 has revealed a stark digital divide in which patients who are older and/or have lower income are less likely to be video-ready. 32 , 33 , 34 , 35 These findings highlight the importance of increasing patient access to video-enabled devices and broadband connectivity to ensure that they are able to successfully engage in video visits. The VHA’s tablet distribution program 36 and the Federal Communications Commissions’ Lifeline program, 37 which offers discounted broadband to individuals with low income, are important steps in this direction.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, COVID-19 has revealed a stark digital divide in which patients who are older and/or have lower income are less likely to be video-ready. 32 , 33 , 34 , 35 These findings highlight the importance of increasing patient access to video-enabled devices and broadband connectivity to ensure that they are able to successfully engage in video visits. The VHA’s tablet distribution program 36 and the Federal Communications Commissions’ Lifeline program, 37 which offers discounted broadband to individuals with low income, are important steps in this direction.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is important to note that the implementation of telehealth to deliver mental health care in the UMHSP Era was largely focused on use of secure video conferencing equipment that allowed specialists physically located at a VAMC to see patients who were physically located at a CBOC 23 . Telehealth delivered outside of the CBOC setting through the VA “Anywhere to Anywhere” initiative was not widely available until 2018 and was not widely used until the start of physical distancing requirements implemented as a result of the COVID‐19 pandemic 47–49 . While the full adoption of more flexible telehealth technology in the VA was spurred by COVID‐19, it is likely to shape mental health access for rural patients for years to come.…”
Section: Discussionmentioning
confidence: 99%
“…23 Telehealth delivered outside of the CBOC setting through the VA "Anywhere to Anywhere" initiative was not widely available until 2018 and was not widely used until the start of physical distancing requirements implemented as a result of the COVID-19 pandemic. [47][48][49] While the full adoption of more flexible telehealth technology in the VA was spurred by COVID-19, it is likely to shape mental health access for rural patients for years to come.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of video mental health visits among US veterans during the COVID-19 pandemic suggests this may be the case. Researchers found that older patients and those with low socioeconomic status had lower odds of completing greater than 50% of their visits via video compared to in-person visits or phone calls [ 17 ]. Taken together, these findings suggest that older veterans with low socioeconomic status, and those experiencing loneliness and social isolation were more likely to face negative mental health consequences of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Among older veterans, many are interested in apps to support health [ 25 ], but tend to have mixed opinions about mental health apps based on sociodemographics such as rurality [ 26 ]. Connolly and colleagues [ 17 ] found that rural veterans are more likely to oppose app usage, describe smartphones as hard to navigate, and cite barriers to usage compared to urban-dwelling populations. However, educational materials and training programs can be successfully implemented to increase older veterans’ comfort with using apps and overcome barriers to utilization [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%